2011
DOI: 10.1097/pas.0b013e318220697f
|View full text |Cite
|
Sign up to set email alerts
|

Grading of Clear Cell Renal Cell Carcinoma Should be Based on Nucleolar Prominence

Abstract: Fuhrman grading of renal cell carcinoma focuses on features of nuclear size, nuclear shape, and nucleolar prominence. Despite the reported widespread usage of Fuhrman grading in clinical studies, there is debate as to the prognostic significance and reproducibility of its criteria. It has been noted that many pathologists rely on assessment of nucleolar prominence alone when grading renal cell carcinoma; however, the validity of this remains unconfirmed. This study was undertaken to determine the relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(71 citation statements)
references
References 0 publications
3
65
0
3
Order By: Relevance
“…They concluded that nucleolar prominence alone held significance for stratifying these tumors [11]. A follow-up study also revealed that nucleolar grade was predictive of survival for clear cell RCC on multivariate analysis, and that alone was a valid grading parameter [35]. These studies suggested that nucleolar prominence independently was a suitable grading system for both clear cell RCC and PRCC [10].…”
Section: Discussionmentioning
confidence: 95%
“…They concluded that nucleolar prominence alone held significance for stratifying these tumors [11]. A follow-up study also revealed that nucleolar grade was predictive of survival for clear cell RCC on multivariate analysis, and that alone was a valid grading parameter [35]. These studies suggested that nucleolar prominence independently was a suitable grading system for both clear cell RCC and PRCC [10].…”
Section: Discussionmentioning
confidence: 95%
“…It was suggested that nucleolar grading alone is a valid grading parameter of CCRCC (Delahunt et al, 2011) et al, 2007). Multiple systems are used to grade RCC of which Furhman's grade is most widely used (Rioux et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Inwieweit diese Parameter voneinander abhängig sind, wurde bisher noch nicht untersucht. In der Praxis ist jedoch Tatsache, dass die meisten Pathologen beim Fuhrman-Grading nahezu ausschließlich die Größe der Nukleolen beurteilen und die beiden anderen Parameter des Fuhrman-Systems (Kerngröße und Kernpolymorphie) weitgehend ignorieren [15]. Einzelne Studien haben für klarzellige Nierenkarzinome gezeigt, dass die Kernform nicht mit der Prognose korreliert und bei papillären Nierenzellkarzinomen ist weder die Kerngröße noch die Kernform von prognostischer Bedeutung [42].…”
Section: Introductionunclassified